Design and simulation of an exhaust based thermoelectric generator (TEG) for waste heat recovery in passenger vehicles - Mohieel El Dien Mansour Saqr, Khalid Mohammed (2008)
The increasing demand for electric power in passenger vehicles has motivated several research focuses since the last two decades. This demand has been revoluted by the unrelenting, rapidly growing reliance on electronics in modern vehicles. Generally, internal combustion engines lose more than 35% of the fuel energy in exhaust gas. Comparing this huge loss to every day's growing oil price, one could understand how the recovery of such losses could help the economy, as well as providing the additional power sources required by contemporary vehicle systems. There are three fundamental advantages of thermoelectric generators (TEGs) over other power sources are three; they do not have any moving parts as they generate power using Seebeck solid-state phenomena, they have a long operation lifetime, and they can be easily integrated to any vehicle's exhaust system. This thesis presents a novel TEG concept aims to resolve the thermal and mechanical disputes faced by the research community. A novel procedure for designing exhaust based TEG is presented as well. Several simulation models are used to analyze the TEG performance. The significance of the novel TEG is discussed through a detailed comparison with experimental results from Clarkson University and Nissan Motors TEG prototype tests. The simulation results showed a huge increase in the energy density achieved by the novel TEG to reach 11.92 W/kg.